EXPATRIATE STUDENTS’ PERCEPTIONS OF KEY FACTORS IMPACTING ATTENDANCE AND PERSISTENCE AT A PRIVATE MALAYSIAN UNIVERSITY: AN ANALYSIS OF A 4PS FRAMEWORK - Deng, Jin; Santos, Ieda M; Mathieu, David J (PUPIL: International Journal of Teaching, Education and Learning, 2018)
Malaysia largely depends on expatriates to develop its economy. The private institution (pseudonym) in Malaysia had not examined the retention of students from expatriate families who might contribute country’s future economy. Assessing the expatriate students’ perceptions of key factors that impacted their attendance and persistence is timely. The purpose of this study was to make recommendations based on the research findings to the private university and possibly other institutions in Malaysia or elsewhere internationally where serve expatriate students to reexamine the practices, amend (if any), and explore additional strategies to improve their attendance, persistence, and graduation rates. Tinto’s model of dropping out guided this study. Three specific research questions were designed to explore expatriate students’ perceptions of individual characteristics, the interactions within the institutional environment, and institutional characteristics respectively that influenced their decisions to attend and persist at the institution. Qualitative data were collected through in-depth interviews with 5 expatriate students. Data analysis followed a thematic approach, resulting in 10 themes. Based on the study outcomes, a white paper was proposed. The purpose of this paper is to present an overview of the study and recommendations to the administrators to increase expatriate students’ persistence and graduate rates either in Malaysia, their country of origin, or elsewhere internationally. The recommendations were based on the 4Ps framework.